CAFFEY’S SYNDROME AND CHILD NEGLECT: A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2022)
Battered baby syndrome also called as Caffey’s syndrome is a term used to define a clinical condition wherein a child receives repetitive physical injuries by parents and caregivers therefore sustaining non accidental traumas. It is considered to be one of the important and usual missed causes of pediatric traumas. It is a crime that is often successfully hidden by its perpetrators. Medical staffs and law enforcement agencies has an important role to play in uncovering these cases of battered child syndrome and gathering evidence for their successful prosecution. The recognition may be difficult because there is no single observation or a sign that is diagnostic for abuse. Here, we report a case where a six years old male child died due to septicemia as a result of combined effect of injuries sustained at different times by the blunt force impact by surface and object and malnutrition.
Keywords: Battered Baby Syndrome; Malnutrition; Pediatric Trauma; Caffey’s Syndrome; Non-Accidental Childhood Trauma